2000
DOI: 10.1136/jcp.53.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Methadone deaths: a toxicological analysis

Abstract: Aims-To perform a toxicological analysis of deaths involving methadone and to determine the fatal concentration of methadone in such deaths. Methods-Deaths in which methadone was mentioned in the cause of death were identified. Deaths were divided into those associated with methadone only and deaths in which the cause of death was a combination of methadone and other drugs. Toxicological findings in these deaths were analysed and compared with previously published data. Results-One hundred and eleven cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 29 publications
7
87
0
3
Order By: Relevance
“…The existence of such high MBL implies a methadone-induced tolerance and enough survival-time for resorption in case of oral application or an intravenous application of a large dosage of methadone [14]. With regard to the increasing age of the deceased in our study an induction of tolerance is quite comprehensible and would also lead to an intake of a higher daily methadone-dosage.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The existence of such high MBL implies a methadone-induced tolerance and enough survival-time for resorption in case of oral application or an intravenous application of a large dosage of methadone [14]. With regard to the increasing age of the deceased in our study an induction of tolerance is quite comprehensible and would also lead to an intake of a higher daily methadone-dosage.…”
Section: Discussionmentioning
confidence: 55%
“…This explains the high mean MBL of 1,324 µg/L and the "usual" median MBL of 700 µg/L. However, many previous investigators have also commented on the difficulty in performing post-mortem toxicologic analyses, interpreting the results and establishing a lethal MBL [3,7,12,14,17,18,22].…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is a strong respiratory depressant, potentially fatal for individuals without sufficient tolerance. 4,5 Buprenorphine is less potent, but if mixed with alcohol or sedatives there is a risk of polydrug intoxication. 6 Both medications have high abuse potential and are sought after on the illicit drug market.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, according to Wolff et al (2000) the median elimination half-life of methadone has been found to be diminished more than 60% when the addict has reached a steadystate methadone level. Thus, patients suffering from addiction who are methadone-naïve are in a high risk of overdosing specifically during the initial phase of methadone maintenance treatment programs (Drummer et al, 1992;Caplehorn and Drummer, 1999;Milroy, 2000;Wolff et al, 2000;Corkery et al, 2004).…”
Section: Limitations Of Existing Resting-state Literaturementioning
confidence: 99%